Cancer patients and loneliness: A systematic review - Cigdem Okten; Zeynep Ozer (Tehran University of Medical Sciences, 2016)
Background & Aim: The number of cancer patients has been continuously increasing due to early diagnosis and the developments in cancer treatment. This has led to an increase in psychosocial problems associated with the diagnoses and treatment of cancer. Loneliness is emphasized to be one of the most frequently observed psychological symptoms in cancer patients. Personal and external factors that cause stress in life and insufficient social support increase the level of loneliness in patients. This systematic review aimed to determine the effect of education and social support provided to the patients diagnosed with cancer on their loneliness. Methods & Materials: This systematic review was prepared in accordance with the Preferred Reporting Items for Systematic review and Meta-Analysis Protocols (PRISMA-P) protocol. The databases of PubMed, CINAHL, ScienceDirect, Web of Science, Cochrane Library, Ulakbim Turkish Medical Index, and Turk Medline were scanned to August 31, 2016, without a limitation of date. The keywords used during the scanning were "cancer and loneliness," and "cancer patients and loneliness." Five studies were included in this review keeping in consideration the inclusion and exclusion criteria. Results: The results of the studies included in this systematic review revealed the positive effect of education and social support on the sense of loneliness observed in cancer patients. Three of five randomized controlled studies found that education and social support positively affected loneliness. Conclusion: The results of this review showed that the education and social support provided to cancer patients should be increased, and sociocultural factors should be considered while planning education and social support.